Leishmania tropica (Kinetoplastida: Trypanosomatidae)--a perplexing parasite - Jacobson, Raymond L (Folia parasitologica, 2003)
Leishmania tropica is one of the causative agents of cutaneous leishmaniasis (CL), a disfiguring parasitic disease that recently was found to be viscerotropic. In urban areas it is transmitted from infected individuals by the bite of phlebotomine sand flies to naïve persons (anthroponotic CL). In rural areas animals are thought to be the reservoir, but the full life cycle is still under investigation (zoonotic CL). For many years L. tropica was either confused or merely grouped with L. major while Phlebotomus sergenti was the only proven vector. In recent years new foci have erupted, but few have been investigated. This review describes some of the history, recent findings, epidemiology, potential vectors, and the search for possible reservoir hosts besides man.
Keywords: leishmanióza kožní; Leishmaniasis, Cutaneous; Insect Vectors; Leishmania tropica; dějiny 20. století; Animals; lidé; History, 20th Century; zdroje nemoci; hmyz - vektory; Humans; zvířata; Phlebotomus; Disease Reservoirs